2010
DOI: 10.1055/s-0030-1263164
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Seizure Activity and Chronic Epilepsy in Early Infancy and Short-Term Neurodevelopmental Outcome Following Fetal Myelomeningocele Closure

Abstract: We explored the relationship between seizure activity (SA) and/or chronic epilepsy (CE) and short-term neurodevelopmental outcomes following fetal myelomeningocele (fMMC) surgery. Retrospective databases and a parental questionnaire focusing on common complications of hindbrain herniation associated with MMC were used to determine the incidence of seizures following fMMC surgery. The Bayley Scales of Infant Development II was used to evaluate the neurocognitive outcomes. The available 3-year outcome data were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 18 publications
0
17
0
1
Order By: Relevance
“…Restoration of CSF volume in the posterior fossa after in utero repair is indicative of reversal of hindbrain herniation. The functional significance is that the vast majority of children demonstrated no or minimal brainstem dysfunction symptoms at followup [21]. The ventriculoperitoneal shunt rate was 46%, which is much lower that the predicted overall shunt rate of 84% based upon 297 historical controls followed at the CHOP Spina Bifida Clinic between 1983 and 2000.…”
Section: Early Clinical Experience At the Children's Hospital Of Philmentioning
confidence: 99%
“…Restoration of CSF volume in the posterior fossa after in utero repair is indicative of reversal of hindbrain herniation. The functional significance is that the vast majority of children demonstrated no or minimal brainstem dysfunction symptoms at followup [21]. The ventriculoperitoneal shunt rate was 46%, which is much lower that the predicted overall shunt rate of 84% based upon 297 historical controls followed at the CHOP Spina Bifida Clinic between 1983 and 2000.…”
Section: Early Clinical Experience At the Children's Hospital Of Philmentioning
confidence: 99%
“…Although these studies also suggest that postnatally repaired MMC patients are at increased risk of developing attention problems, significant attention deficits were not found in our cohort. Of note, our previous follow-up evaluations of children who underwent fMMC surgery at our institution also demonstrated that children who required ventriculoperitoneal shunting following fetal intervention were more likely to continue to present with Chiari II malformationrelated neurological dysfunction, a higher incidence of seizure activity and had lower neurocognitive scores compared to those fMMC children who did not require a shunt [12,13,15,16] . We can only speculate whether children who require shunt placement have more extensive underlying dysgenesis or disorganization of their brain such as increased reduction in cerebral white matter and overall cortical mantle, and/or abnormalities involving the midbrain, cerebellum and corpus callosum that allow a more frequent manifestation of neurocognitive and neurobehavioral problems than their non-shunted fMMC peers.…”
Section: Discussionmentioning
confidence: 66%
“…On average, fMMC children are born at 34 weeks of gestation with 14% of infants born before 30 weeks of gestation in our initial non-randomized fMMC cohort and with 13% of infants in the NIHsponsored randomized MOMS trial [9,17] . Although the impact of fMMC surgery on neurocognitive and neurofunctional outcome has been examined extensively [10,[12][13][14][15][16][17] , less attention has been paid to the impact of fMMC repair on the overall neurobehavioral outcome. Therefore, we examined the preschool neurobehavioral outcome in children who underwent fMMC prior to the initiation of the NIH-sponsored randomized trial.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to historical controls, it was estimated that fMMC surgery may reduce the need for ventriculoperitoneal shunt placement from 80-90 to 40% [9] . The functional significance of the more normal position of the hindbrain, reduced shunt rate and restoration of nearnormal CSF hydrodynamics [68,69] is that the vast majority of fMMC children demonstrated absent to mild brain stem dysfunction symptoms at 6 years of follow-up [70,71] .…”
Section: Nonrandomized Resultsmentioning
confidence: 99%